2010
DOI: 10.1155/2010/329587
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis of the Gastroduodenal Groove: A Case Report

Abstract: Groove pancreatitis, a form of chronic pancreatitis affecting the head of the pancreas, is localized within the groove between the pancreas head, duodenum, and common bile duct. We report a case of a male patient with groove pancreatitis who initially underwent a duodenal preserving gastrenteranastomosis. Unfortunately, the patient's symptoms were only partially controlled, necessitating a pancreaticoduodenectomy in due course as the definite surgical restoration procedure. The surgical approach selected prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…It has also been reported that diarrhea or diabetes mellitus are commonly associated with GP (15). The clinical symptoms of the syndrome spread over the time span ranging from a few weeks to a year, then the GP becomes chronic (16). In a high number of patients with alcohol abuse, obstructive jaundice has been observed especially in the course of chronic disease if late stenosis of the CBD has occurred (17).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It has also been reported that diarrhea or diabetes mellitus are commonly associated with GP (15). The clinical symptoms of the syndrome spread over the time span ranging from a few weeks to a year, then the GP becomes chronic (16). In a high number of patients with alcohol abuse, obstructive jaundice has been observed especially in the course of chronic disease if late stenosis of the CBD has occurred (17).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Thus, PD is considered to be an invasive procedure for GP treatment. DPPHR has also been performed in certain cases and has achieved satisfactory results of symptom relief ( 3 , 4 , 8 ). Another technique is PPDR, which is particularly suitable for cases with significant duodenal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of GP remains unclear, and a specific treatment strategy has yet to be established ( 4 ). The reported treatments of GP include medical ( 3 , 4 ), endoscopic ( 5 ) or surgical approaches ( 3 , 4 , 6 8 ), according to the clinical features of the condition. The main drawback of nonsurgical approaches is the high risk of recurrence of symptoms subsequent to treatment cessation ( 5 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La presencia de ictericia es usualmente fluctuante, excepto cuando cursa con cáncer de páncreas o colangitis (18,19). El curso de la enfermedad es crónico, y puede ser de años en relación con la aparición de los síntomas y el diagnóstico (20).…”
Section: Presentación Clínicaunclassified